A "figure of merit" for susceptibility of irradiated amorphous metal alloys to thermal spike-induced plasticity. (1st January 2016) - Baumer, Richard E.; Demkowicz, Michael J.
Abstract: Thermal spikes in irradiated amorphous metal alloys emit stress pulses of sufficient intensity to trigger plastic deformation in adjacent unmelted material. This localized plasticity may lead to macro-scale anisotropic shape changes in metallic glasses under neutron or ion irradiation, even in the absence of external loading. We formulate a micromechanical model that connects thermal spike-induced plasticity (TSIP) to bulk properties of amorphous metal alloys. This model gives rise to a "figure of merit" (FOM) for ranking the susceptibility of metallic glasses to TSIP without recourse to further experiments or simulations. We validate the FOM against molecular dynamics simulations of TSIP in amorphous Cu–Nb alloys. Graphical abstract: